Percutaneous Nephrolithotomy vs. Retrograde Intrarenal Surgery for Renal Stones Larger than 2cm in Patients with a Solitary Kidney: A Systematic Review and a Meta-Analysis - Jiang, Kehua; Zhang, Peng; Xu, Bin; Luo, Guangheng; Hu, Jianxing; Zhu, Jianguo; Sun, Fa (Urology Journal, 2020)
Purpose: The safety and feasibility of percutaneous nephrolithotomy (PCNL) compared with retrograde intrarenal surgery (RIRS) are debated. This systematic evaluation was performed to obtain comprehensive evidence with regard to the treatment outcomes of PCNL compared with RIRS for management of renal stones in patients with solitary kidney. Material and Methods: A systematic search of Medline, Embase, Pubmed, Web of Science, CNKI, Scopus and the Cochrane Library was performed to identify studies that compared PCNL with RIRS for management of renal stones in patients with solitary kidney and published up to Aug 2019. Outcomes of interest included perioperative variables, complications, and stone-free rate (SFR). Results: Four studies assessing PCNL vs. RIRS for renal stones larger than 2cm were included for meta-analysis. Although patients underwent PCNL have higher initial SFR than RIRS (OR: 3.72, 95% CI:2.38 to 5.83; P＜0.001), patients underwent RIRS have less intraoperative blood loss (dropped Hb: WMD= 3.49 g/L, 95% CI:2.83 to 4.15; P＜0.001), lower blood transfusion rates (OR= 5.31, 95% CI:1.36 to 20.68; P=0.02), and higher incidence rate of steinstrasse (OR:0.20, 95% CI:0.04 to 0.91; P=0.04). All the other calculated results including operation time (WMD: -9.87 minute, 95% CI:-30.11 to 10.37; P=0.34), final SFR (OR:1.65, 95% CI:0.80 to 3.42;P=0.18) and overall complications (OR:1.22, 95% CI:0.78 to 1.93; P=0.38) are similar between the two groups. Conclusion: Our results indicate that PCNL has higher initial SFR than RIRS in the treatment of renal stones larger than 2cm in patients with a solitary kidney, the overall complications were similar in both groups. However, RIRS, with less blood loss and transfusion rate, may be an alternative in selected patients. But we need to pay more attention to the incidence rate of steinstrasse after RIRS.